El Cid torero: de la literatura al arte - José María Díez Borque (Anales de Historia del Arte, 2008)
The motif of The Cid as bullfighter is extremely rare in the iconography and literature relating to this Spanish medieval hero. The author examines Goya’s preparatory drawings and print of “The Cid Campeador spearing another bull” (La Tauromaquia, plate 11) and the Mojiganga del Cid para fiestas del Señor, in which The Cid triumphs as a bullfighter. This 17th-century literary masquerade precedes Nicolás Fernández de Moratín’s 18th-century Fiesta de toros en Madrid, so often associated by the critics with Goya’s bullfight imagery.